2015
DOI: 10.1038/ncomms7620
|View full text |Cite
|
Sign up to set email alerts
|

Single-step deposition of high-mobility graphene at reduced temperatures

Abstract: Current methods of chemical vapour deposition (CVD) of graphene on copper are complicated by multiple processing steps and by high temperatures required in both preparing the copper and inducing subsequent film growth. Here we demonstrate a plasma-enhanced CVD chemistry that enables the entire process to take place in a single step, at reduced temperatures (o420°C), and in a matter of minutes. Growth on copper foils is found to nucleate from arrays of well-aligned domains, and the ensuing films possess sub-nan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(125 citation statements)
references
References 30 publications
(78 reference statements)
8
116
1
Order By: Relevance
“…This low photocatalytic performance may be attributed to the fast charge recombination [44,45]. Graphene thin film also shows a poor involvement in chemical conversion, as observed by others also, e.g., [46], here about 5% after 60 min. In the case of graphene-TiO 2 thin films, it is observed that under illumination, the spin-SVPT and SVASC samples linearly degrade the contaminant, and after 60 min about 77% and 84% of MB in water is removed, respectively.…”
Section: Resultsmentioning
confidence: 72%
“…This low photocatalytic performance may be attributed to the fast charge recombination [44,45]. Graphene thin film also shows a poor involvement in chemical conversion, as observed by others also, e.g., [46], here about 5% after 60 min. In the case of graphene-TiO 2 thin films, it is observed that under illumination, the spin-SVPT and SVASC samples linearly degrade the contaminant, and after 60 min about 77% and 84% of MB in water is removed, respectively.…”
Section: Resultsmentioning
confidence: 72%
“…Low Temperature Plasma CVD Grown Graphene by Microwave Surface-Wave Plasma CVD Using Camphor Precursor 38 substrates as suggest by Boyd et al [11]. Present results show that camphor precursor could be the best choice for graphene growth at low temperature as oxygen present in the camphor molecule is seen to be beneficial for both controlling the thickness and passivating Cu substrate during growth.…”
Section: -Probe Sheet Resistance Transmissionmentioning
confidence: 51%
“…Moreover, the film deposited using camphor shows superior quality than that of the film deposited by using methane. Other defect related peaks such as D` peak around 1,625 cm -1 (shoulder peak of G peak) [5,11] and the peak around 2,944 cm -1 is reduced preciously while placing cover above the substrate during growth. These two defect-related peaks are almost invisible in the case of the film deposited by using camphor precursor, which indicates the merit of carbon source (a) with direct exposure of substrate to plasma; (b) avoiding direct exposure of substrate to plasma.…”
Section: Resultsmentioning
confidence: 99%
“…For the purposes of this review, it is interesting to focus on a few unique features of graphene, such as its high mobility and wide carrier concentration tuning range. Room temperature mobilities, which can be as high as ~10 5 cm 2 V −1 s −1 [21,22], and carrier concentration modulations, up to ~10 14 cm −2 [23], make graphene attractive because they provide a wider spanning range useful for active modulation. The optical conductivity in graphene at THz frequency is well described by the Kubo formula [24] considering only the intraband contribution.…”
Section: Basic Theoretical Principlementioning
confidence: 99%